Prediction of pressure drop in heavy oil water ring based on modified two fluid model - Jiqiang Fu; Mingjun Du; Jiaqiang Jing; Huichao Liu; Jie Sun; Weicong Chen; Yongjiu Chen (Scientific Reports)
Abstract Accurate prediction of pressure drop of the heavy oil-water ring flow in pipeline is of great significance for establishing an optimal drag reduction model and ensuring safe production. The effects of different factors on the flow pattern and pressure drop of heavy oil-water annular two-phase flow were systematically analyzed, and a standard two-fluid pressure drop prediction model for annular flow was established. By modifying the shear stress equation of oil-water interface and introducing the wave-flow theory to modify the shear stress equation of water wall, a pressure drop prediction model for the generalized concentric water ring was obtained to calculate the periodic fluctuations of oil phase. Furthermore, by introducing the comprehensive Reynolds number expression of eccentric water ring, the pressure drop prediction model for the generalized eccentric water ring was obtained to calculate the periodic fluctuations of oil phase. The results show that the pressure drop prediction accuracy of the concentric water ring for ultra-heavy oil is improved by 80% by using the modified pressure drop prediction model. The comprehensive Reynolds number expression of eccentric water ring can effectively reflect the influence of eccentric effect on shear stress of water wall and the calculation error is less than 20% by predicting the pressure drop of the generalized eccentric water ring with different density differences.